2015
DOI: 10.1007/s11277-015-2935-8
|View full text |Cite
|
Sign up to set email alerts
|

Non-contiguous Channel Bonding for TV White Space Usage with NC-OFDM Transmission

Abstract: Contiguous channel bonding for using more than one channels together in TV white space has been considered in the IEEE 802.22-specified wireless regional area network system. To support more flexible channel usage, this paper investigates noncontiguous channel bonding as a potential extended feature of IEEE 802.22 standard. The transceiver structure with Non-Contiguous OFDM (NC-OFDM) transmission to support non-contiguous channel bonding is presented. The simulation results show that non-contiguous channel bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…The SINR and collision-protocol models designed in [22] are also suitable for shared access in rotating weather radar systems, and the SINR model with non-contiguous CB is used in our proposed system. The results showed that the non-adjacent channels scenario has a higher averaged sum data rate in [22] and [12] also proved that non-contiguous CB is more flexible and can provide a higher data rate than contiguous CB.…”
Section: Related Literaturementioning
confidence: 77%
See 1 more Smart Citation
“…The SINR and collision-protocol models designed in [22] are also suitable for shared access in rotating weather radar systems, and the SINR model with non-contiguous CB is used in our proposed system. The results showed that the non-adjacent channels scenario has a higher averaged sum data rate in [22] and [12] also proved that non-contiguous CB is more flexible and can provide a higher data rate than contiguous CB.…”
Section: Related Literaturementioning
confidence: 77%
“…There are two main types of CB methods: contiguous CB which aggregates the adjacent available channels to combine as a common larger channel for better data rate, and non-contiguous CB which allows to aggregate the available channels even if they are not adjacent. Non-contiguous CB is widely used in cognitive radio technologies due to its flexibility and higher data rate than contiguous CB [12]. Therefore, we propose an efficient sharing and radar protection system which consists of two parts of algorithms with the aid of cloud-based REM using predicted time series of interference at the radar and non-contiguous channel bonding technique.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous paper, 10 the flexibility of using channels has been validated, where the transceiver structure has been designed with noncontiguous (NC) OFDM (NC‐OFDM) transmission. Here, the transmission scheme supports noncontiguous CB.…”
Section: Related Studies On Cbmentioning
confidence: 99%
“…CA is the bundling of two or more carriers or channels into one solitary data channel to enhance data capacity. CA has its drawbacks, where tight synchronization is needed and more overhead is involved in the control message 10 . In LTE‐Advanced, the downside of CA is adaptability for aggregating any sort of spectrum sections that are restricted and several resource blocks (RBs) can be utilized for data communication.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation